The underground city, with ebook eaudiobook - Verne, Jules (Tantor Media, 2009)
How can humans survive and prosper 1,500 feet below the earth's surface? Jules Verne successfully weaves a dark yet magnificent story into this equally dark world. The book takes place in a revived and now prosperous coal mine. Amazingly, life in the mine has everything that one could desire, including a lake, fish, and attractive homes. Yet there lurks an evil presence: unexplainable, malicious, and life-threatening occurrences begin. And this evil force could destroy the underground world and everyone in it.